Detection of nodules of the thyroid gland, by ultrasonographic study, in patient volunteers - Ureta Núñez, Yonny Manuel (2011)
Objective: To determine the prevalence of thyroid nodules in a voluntary population of the city of Arequipa has no personal history of thyroid disease. Material and methods: 214 patients were included in the city of Arequipa adult volunteers without a history of thyroid disease and no evidence of active neoplastic disease, to which was performed thyroid ultrasound, collect epidemiological data, age, sex, BMI , smoking, family history of thyroid disease, history of cardiovascular disease, history of metabolic disease. Results: We identified 48 patients with thyroid nodules, of which 9 were males and 39 females, of these 5 (1 woman and 4 men) had a history of smoking, 10 had a family history of thyroid disease (9 women and 1 man), 5 history of cardiovascular disease (3 women and 2 men) and 4 (women) a history of metabolic diseases. The average age of patients with nodules was 47.8 for men and 45 women. We found 110 patients with a BMI corresponding to Pre Obesity, 26 obese patients with type I, 3 obese type II and 4 with acceptable thinness. Conclusions: The prevalence of thyroid nodules detected is similar to world literature. We observed a tendency to have thyroid nodules in women whose average age was 45 years and men 47.8 years, no association with smoking and / or family history. These observations require a larger sample and calculated based on probabilistic methods to strengthen our conclusions.